P052 Biosimilar BI 695501 Demonstrates Non-Inferior Efficacy and Comparable Safety to Adalimumab Reference Product in Patients With Active Crohn's Disease. (December 2019) - Hanauer, Stephen; Schreiber, Stefan; Balser, Sigrid; Liedert, Bernd
Abstract : BACKGROUND: BI 695501 has demonstrated bioequivalence to both the US-licensed and EU-approved adalimumab reference product (RP) in rheumatoid arthritis. The aim of this head-to-head trial was to evaluate the similarity of BI 695501 and EU-approved adalimumab RP, by comparing efficacy, endoscopic improvement, safety, pharmacokinetics and immunogenicity in patients with active Crohn's disease. Here we present the Week 4 primary endpoint assessment and safety data up to Week 24. METHODS: In this Phase III, 56-week, randomized, double-blind, multicenter, parallel-group, non-inferiority study (NCT02871635), 147 patients were randomized 1:1 to receive BI 695501 or EU-approved adalimumab RP (160 mg loading dose on Day 1, 80 mg on Day 15, and 40 mg every 2 weeks thereafter). Patients were stratified by prior exposure to infliximab (Yes, No) and Simple Endoscopic Score for Crohn's Disease (≥16, <16). Primary endpoint was Crohn's Disease Activity Index (CDAI) response (decrease ≥70) at Week 4, with an exploratory non-inferiority margin of 0.76. Secondary endpoints included Week 24 CDAI response and clinical remission. After 4 weeks, responders continued a maintenance phase up to 24 weeks, at which point adalimumab RP patients were switched to BI 695501. Patient populations used in the primary analyses were the full analysis set (FAS; BI 695501: n = 68; adalimumab RP: n = 72), safety analysis set (SAF; BI 695501: n = 72; adalimumab RP: n = 75), and per protocol set (PPS; BI 695501: n = 66; adalimumab RP: n = 68). RESULTS: Patient demographics, baseline characteristics and stratification factors were balanced between treatment groups. Response and remission rates in the populations recruited were high. Similar response rates were observed in both treatment groups for the primary endpoint of ≥70 decrease in CDAI (BI 695501 89.7%; adalimumab RP 94.4%), and the lower bounds of the confidence intervals (CI) were above the exploratory non-inferiority limit of 0.76 (relative risk [RR] 0.945 [90% CI: 0.870, 1.028; 95% CI: 0.856, 1.044]). The results of a sensitivity analysis using the PPS supported the primary analysis (BI 695501 90.9%; adalimumab RP [RR] 0.941 [90% CI: 0.872, 1.015; 95% CI: 0.859, 1.030]). An exploratory efficacy analysis found similar treatment effects in CDAI score at Week 4 as well as in decrease in CDAI ≥100, and absolute CDAI <150 during the induction phase in both treatment groups. BI 695501 and adalimumab RP demonstrated similar safety profiles up to 24 weeks (any adverse event [AE]: BI 695501 41.7%; adalimumab RP 36.0%; serious AEs: BI 695501 2.8%; adalimumab 4.0%) with no unexpected safety signals. AE of special interst were low (BI 695501 1.4%; adalimumab RP 2.7%) and infections reported were similar for both treatment groups (BI 695501 13.9%; adalimumab RP 14.7%). Injection site reactions were more commonly noted with adalimumab RP (BI 695501 0%; adalimumab RP 4.0%). CONCLUSION(S): In a primary analysis based on efficacy data up to Week 4, BI 695501 demonstrated non-inferior efficacy compared with adalimumab RP in patients with active Crohn's disease. Moreover, safety profiles up to 24 weeks were similar between treatment arms. Response and remission rates appear to be higher in actively controlled trials than in those using placebo.